Annealing aged zirconia: Study of surface mechanical properties at the micrometric length scale. Issue 3 (March 2015) - Roa, J.J.; Anglada, M.
Abstract: The annealing of hydrothermal aged zirconia has been studied by analysing the changes in microstructure and surface mechanical properties in terms of the annealing temperature. In this experimental work, a systematic micro- and nanomechanical study has been conducted in 3 mol% yttria-stabilized tetragonal polycrystalline zirconia (3Y-TZP) aged at 134 °C for 60 h and annealed at 600 °C and 850 °C for 1 h. Advance characterization techniques (micro-Raman, field emission scanning electron microscopy and focused ion beam) have been used to study the near surface microstructural changes induced by these treatments. The mechanical properties and resistance to damage of the near surface are determined by means of nanoindentation and nanoscratch testing. The observed behaviour is discussed in terms of the change in microstructure induced after ageing and annealing.